2004
DOI: 10.1111/j.1365-2672.2004.02380.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and prevalence of Salmonella in beef cattle presenting at slaughter

Abstract: Methods and Results: Automated immunomagnetic separation (AIMS) was used for detection and isolation of Salmonella enriched from cattle faeces. Salmonella were enumerated from positive samples using a combination of the Most Probable Number (MPN) technique and AIMS. A total of 310 faecal samples were tested, 155 were from lot-fed cattle and 155 from grass-fed cattle. Salmonella spp. were isolated from 21 (6AE8%) of the cattle and the prevalence amongst grass-fed cattle (4AE5%) was not significantly different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 30 publications
(42 reference statements)
3
34
2
Order By: Relevance
“…Salmonella Typhimurium and Salmonella Newport were the most frequently isolated serovars, each accounting for 21.4% of the total isolates. The frequency of isolation of Salmonella Typhimurium was consistent with the report of Alemayehu et al (2003) and Fegan et al (2004) who found Salmonella Typhimurium as being the dominant serovar among their isolates. Salmonella Infantis and Salmonella Mishmarhaemek were detected with prevalences of 17.9% and 7.1%, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Salmonella Typhimurium and Salmonella Newport were the most frequently isolated serovars, each accounting for 21.4% of the total isolates. The frequency of isolation of Salmonella Typhimurium was consistent with the report of Alemayehu et al (2003) and Fegan et al (2004) who found Salmonella Typhimurium as being the dominant serovar among their isolates. Salmonella Infantis and Salmonella Mishmarhaemek were detected with prevalences of 17.9% and 7.1%, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of Salmonella from carcasses was in agreement with the work of Alemayehu et al (2003) who reported prevalence of 3.1% and 2.8% from muscles of the diaphragm and the abdomen, respectively. Fegan et al (2004) also reported carcass contamination of 2% from an abattoir in Australia. In any case, carcass contamination levels have to be taken with caution; as the presence of even a single carrier animal can be a potential source of contamination of the carcasses, environment or personnel.…”
Section: Discussionmentioning
confidence: 91%
“…In this study the prevalence (20%) is much higher than that reported by Fegan et al, (2004) in Australia, which was 6.88%. In the United States, the prevalence of Salmonella in cattle faeces in farms was reported to be less than 7% (Losinger et al, 1997;Fedorka-Cray et al, 1998;Dargatzet et al, 2003).…”
Section: Phenotypes Of Resistant Serovarscontrasting
confidence: 47%
“…Other researchers (Dargatz et al, 2000) have reported a lower prevalence (1.4 to 4.5%) than that observed by Theis et al (2005Theis et al ( , 2007 while others (Fegan et al, 2004) have reported Salmonella prevalence as high as 16%. It is possible that the lower prevalence reported by Theis et al (2005Theis et al ( , 2007 could have been attributed to the smaller sample (N =212) of cattle compared to that of other researchers.…”
Section: Salmonella From Ranch Cattlecontrasting
confidence: 45%